2009
DOI: 10.1007/s10563-009-9069-5
|View full text |Cite
|
Sign up to set email alerts
|

Production of 1,3-Butadiene From C4 Raffinate-3 Through Oxidative Dehydrogenation of n-Butene Over Bismuth Molybdate Catalysts

Abstract: Recent progress on the bismuth molybdate catalysts for oxidative dehydrogenation of n-butene to 1, 3-butadiene was reported in this review. A number of bismuth molybdate catalysts, including pure bismuth molybdates (a-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Later, they were found to be capable of catalyzing the ammoxidation of propylene to acrylonitrile and the oxidation of propylene to acrolein . Their potential for further catalytic processes was extensively studied thereafter . Nowadays, they have became popular catalysts for the oxidation of light hydrocarbons .…”
Section: Introductionsupporting
confidence: 88%
“…Later, they were found to be capable of catalyzing the ammoxidation of propylene to acrylonitrile and the oxidation of propylene to acrolein . Their potential for further catalytic processes was extensively studied thereafter . Nowadays, they have became popular catalysts for the oxidation of light hydrocarbons .…”
Section: Introductionsupporting
confidence: 88%
“…33 At the same time, Molybdenum bismuth catalysts have been widely concerned in the field of oxidative dehydrogenation owing to their redox properties. [34][35][36][37] They have good stability and catalytic activity in the oxidation, and more importantly, some observation indicated that their catalytic performances could be changed along with altering the pH value in the prepared procedure. 38,39 Although great efforts had been devoted to the development of effective progress for the production of DFF from bio-based furan derivatives, most of these approaches suffer from one or more shortcomings, such as low yield, tedious work-up processes, difficulty in reusability of the catalyst, and poor selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…could bring out DFF with 99% yield in p ‐chlorotoluene 33 . At the same time, Molybdenum bismuth catalysts have been widely concerned in the field of oxidative dehydrogenation owing to their redox properties 34‐37 . They have good stability and catalytic activity in the oxidation, and more importantly, some observation indicated that their catalytic performances could be changed along with altering the pH value in the prepared procedure 38,39 …”
Section: Introductionmentioning
confidence: 99%